Utilization of Facebook & Instagram Social Media as Media for Learning Arabic in Indonesia: Pemanfaatan Media Sosial Facebook & Instagram Sebagai Media Pembelajaran Bahasa Arab di Indonesia - Nurul Huda; Hamasliko Mahdawati; Aulia Karima Zuhda Utami (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2023)
This research is a descriptive-qualitative study that aims to describe how the use of social media (Facebook and Instagram) affects the process of Arabic teaching and learning in Indonesia. Social media do not only have functions as entertainment but also as education. The research objects are the Facebook group learning Arabic and Instagram @Arabiyahtalks. Data collection techniques used in this research included observation, interviews, and documentation. Meanwhile, data analysis techniques use the models of interactive data analysis that have been developed by Miles and Huberman, namely: data collection, data reduction, data explanation, and conclusions. The results of this research show that: The use of social media facebook & instagram as Arabic media learning that conducted by the Account Group Facebook of Arabic Learning and Instagram @Arabiyahtalks included in the pattern of media utilization outside the classroom situation. The management of the two accounts is independent, regardless of formal educational institutions, and does not refer to the curriculum in schools or madrasahs. Abstrak Penelitian ini merupakan penelitian deskriptif-kualitatif yang bertujuan untuk mendeskripsikan bagaimana pemanfaatan media sosial facebook dan instagram dalam proses pembelajaran bahasa Arab di Indonesia, sehingga media sosial tidak hanya berfungsi sebagai hiburan tetapi juga sebagai pendidikan. Obyek penelitian adalah Grup facebook belajar bahasa Arab dan Instagram @Arabiyahtalks. Teknik pengumpulan data dalam penelitian ini menggunakan observasi, wawancara dan dokumentasi. Sedangkan teknik analisis data menggunakan model analisis data interaktif yang telah dikembangkan oleh Miles & Huberman yaitu: pengumpulan data, reduksi data, penjelasan data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: Penggunaan media sosial facebook & instagram sebagai media pembelajaran bahasa Arab yang dilakukan oleh Grup Akun Facebook Pembelajaran Bahasa Arab dan Instagram @Arabiyahtalks termasuk dalam pola pemanfaatan media di luar situasi kelas. Pengelolaan kedua akun tersebut bersifat mandiri, terlepas dari lembaga pendidikan formal dan tidak mengacu pada kurikulum di sekolah atau madrasah.